The THE ROLE OF INTERNAL AUDIT IN PROMOTING ORGANISATIONAL ETHICS AND INTEGRITY - Josephine Eyra Geraldo (Journal of Business Management and Accounting, 2025)
Internal auditing has evolved from a traditional compliance function into a strategic mechanism for promoting ethical governance and institutional integrity. Amid increasing public scrutiny over corruption, unethical conduct, and fragile accountability, particularly in public sector institutions, there has been less research to assess how it affects these practices. This paper critically examines the underexplored yet vital role of internal audit in fostering organisational ethics and integrity. The findings reveal that internal audit possesses significant but underleveraged potential in promoting ethical culture and values. Key barriers include insufficient support from top management, inadequate resources, weak integration of ethics into audit planning, and pervasive negative perceptions of the audit function. The study further identifies structural, cultural, and institutional factors that limit the ethical influence of internal auditors.